(untitled) (Swiss Medical Weekly, 2022)
AIM OF THE STUDY: Kawasaki disease is a febrile illness which can lead to significant coronary artery lesions. Its incidence varies among countries and is highest in Japan (330.2 children under 5 years old/100,000 per year). Since the epidemiology of Kawasaki disease in Switzerland is unknown, we conducted a national prospective data collection between 2013 and 2017 to describe its incidence, diagnosis, and treatment. METHODS: We collected demographic and clinical data of the children under 17 years old hospitalised with Kawasaki disease in Switzerland between March 2013 and February 2017 using anonymous data collection forms with the help of the Swiss Paediatric Surveillance Unit (SPSU). We defined Kawasaki disease per the 2004 American Heart Association criteria: patients with ≥5 days of fever and ≥4 of the 5 main clinical features were included as complete Kawasaki disease and patients with ≥5 days of fever and <4 of the 5 main clinical features were included as incomplete Kawasaki disease. The incidence was calculated with the data of the Federal Statistical Office of Switzerland, considering permanent residents of the country. The different groups were compared by the unpaired student t-test for continuous variables and Pearson’s chi squared test for categorical variables, respectively. RESULTS: We included 175 patients: 60% were boys, with a mean age of 38.2 months. The incidence of Kawasaki disease was 3.1/100,000 [95% CI 2.6–3.7] per year in children under 17 years of age and 8.4/100,000 [95% CI 6.7–10.2] per year in children under 5 years of age. The most frequent clinical signs were a rash (85.4%) and changes of the lips and oral/pharyngeal mucosa (83.4%). The diagnosis of Kawasaki disease was made at a mean of 7.3 days after the first symptom. Echocardiography was abnormal in 52.3%. The treatment with intravenous immunoglobulins (IVIG) and acetylsalicylic acid was administered in accordance with international guidelines. Subgroup analysis showed that children older than 5 years old had significantly more complete Kawasaki disease than the younger ones (78.8% vs 57.4%, p = 0.021). Children with “extreme ages” (<1 year old and >8 years old) were diagnosed later (8.6 (±0.9) vs 7.0 (±0.3) days, p = 0.0129), had longer duration of fever (9.8 (±0.9) vs 8.1 (±0.3) days, p = 0.013) and had more echocardiographic abnormalities (n = 26 (70.3%) vs n = 65 (47.5%), p = 0.014) at diagnosis. One child died during the acute phase of the illness. CONCLUSIONS: The incidence of Kawasaki disease in Switzerland is in the lower range of other European countries.